The city of Yakutsk: a case of study for human brown adipose tissue in extremely cold conditions ... - Severi, Ilenia; Innokentevich, Tomskii Mikhail; Gavrilievich, Tikhonov Dmitrii; Savvichna, Loskutova Kiunniai; Andreevich, Isakov Evgeny; Giordano, Antonio; Gesuita, Rosaria; Cinti, Saverio (Italian Journal of Anatomy and Embryology, 2015)
The discovery of the presence of functional brown adipose tissue (BAT) also in healthy humans [1-3] has focused the attention of the scientific community on the possibility to expand body BAT content as a therapeutic strategy for the treatment and prevention of obesity and the associated metabolic disorders. Indeed, white-to- brown adipocyte transdifferentiation, leading to “browning” of the adipose organ, has been shown to reduce body weight and improve metabolic parameters in obese and insulin-resistant animal models. BAT from subject exposed daily to extremely cold outdoor temperatures has never been studied through morphological techniques. In this context, an exciting case of study are the citizens of Yakutsk, an East- ern Siberian population exposed to the annual average temperature of -10 °C, that peaks up to -50°C during winter. In autoptic fat biopsies from a 54-year-old patient living in Yakutsk BAT is present in the perirenal and para-aortic fat specimens. Importantly, the mean adipocyte area of ... : Italian Journal of Anatomy and Embryology, Vol. 120, No. 1 (Supplement) 2015 ...